The Effect of Istighosah's Devotion to Reducing the Anxiety Level of Santri in Facing Life's Problems (Journal Intellectual Sufism Research (JISR), 2023)
This research aims to determine the effect of istighosah's solemnity on the level of anxiety in facing life's problems. This type of research is correlational quantitative. The research was conducted on all students of the Jagad 'Alimussirry Islamic Boarding School, Surabaya. The data were obtained from questionnaires filled out by the research subjects ( self-rating scales ) and then analyzed using quantitative methods to obtain an overview of the level of istighosah and the level of anxiety of students in facing life's problems. The results showed that there was a significant influence between the level of solemnity in carrying out istighosah experienced by Jagad 'Alimussirry Islamic Boarding School students in facing life's problems with a significance value of 0.038